Removal of a thin hydrogenated carbon film by oxygen plasma treatment - Cvelbar, Uroš (Materiali in tehnologije, 2011)
Capability of low pressure oxygen as a medium for removal of hydrogenated carbon thin films is demonstrated. The film was deposited onto polished iron discs by CVD method. Discs were mounted into a discharge chamber which was evacuated to the ultimate pressure of about 5 Pa. Methane of commercial puritywas leaked into the chamber during continuous pumping so the pressure of 100 Pa was established. Weakly ionized plasma was then created in the chamber by an inductively coupled RF generator operating at the frequency of 27.12 MHz and the power of about 200 W. The methane molecules dissociated in the plasma forming CHx radicals that adsorbed on the sample surface causing formation of a thin film of hydrogenated carbon. AES depth profiling showed that a 3 nm thick film was formed after 200 s of plasma treatment. Samples were then exposed to oxygen plasma in the same chamber, and characterized by AES as well as water drop contact angle. After 12 s of oxygen plasma treatmentthe samples were visually free of carbon and the AES depth profiling proved it. The contact angle of a water drop decreased from initial 80° to about 10° indicating a rapid transformation of the surface properties from hydrophobic to hydrophilic character. The experiments allowed for estimation of the cleaning efficiency which was about 0.25 nm/s.
Keywords: hidrogeniranje; plazma; ogljik; metan; kisik; Augerjeva spektroskopija